Compounds Isolated from the Leaf of Sanchezia Nobilis Hook.f. - Bui, Thi Xuan (H. : ĐHQGHN, 2019)
The ethylacetate fraction of the leaf of Sanchezia nobilis Hook.f. collected in Nam Dinh province isolated two compounds, daucosterol and stigmasterol, for the first time by chromatographic methods. Their structures were elucidated by spectroscopic methods, including MS and NMR